UNDERSTANDING DIFFERENTIAL ASSOCIATION AND GENERAL STRAIN THEORIES TO ANALYZE SUICIDE BOMBING IN INDONESIA - Alfons Zakaria (Arena Hukum, 2012)
On Friday 21st April 2011, Indonesia was shocked by a suicide bombing in a police mosque in Cirebon,West Java Indonesia. The bombing exploded just before the Friday prayer began. Historically, althoughsuicide bombings or mosque bombing have occurred elsewhere, the suicide mosque bombing in Cirebonwas the first time this had occurred in Indonesia. There are similarities between the Cirebon bombingand other bombings occurring in Indonesia. First, there is a similar relationship among the suspects.Second, the suspects were all involved in organizations that have hard-line Islamic ideology. The aim ofthis paper is to understand the differential association and general strain theories in the light of the newform suicide bombing that occurred in Indonesia. This paper will be argued that differential associationtheory is an appropriate approach to explain the cause of the suicide bombing related to the relationshipamong suspects. Similarly, general strain theory is a suitable approach to explain the cause of theterrorism in Indonesia.KeyWords: terrorism, suicide bombing, differential association and general strain theories.